Role of Primary Afferents in Arthritis Induced Spinal Microglial Reactivity - Kwok, Charlie H. T.; Kohro, Yuta; Mousseau, Michael; O’Brien, Melissa S.; Matyas, John R.; McDougall, Jason J.; Trang, Tuan (Frontiers in Immunology, 2021)
Increased afferent input resulting from painful injury augments the activity of central nociceptive circuits via both neuron-neuron and neuron-glia interactions. Microglia, resident immune cells of the central nervous system (CNS), play a crucial role in the pathogenesis of chronic pain. This study provides a framework for understanding how peripheral joint injury signals the CNS to engage spinal microglial responses. During the first week of monosodium iodoacetate (MIA)-induced knee joint injury in male rats, inflammatory and neuropathic pain were characterized by increased firing of peripheral joint afferents. This increased peripheral afferent activity was accompanied by increased Iba1 immunoreactivity within the spinal dorsal horn indicating microglial activation. Pharmacological silencing of C and A afferents with co-injections of QX-314 and bupivacaine, capsaicin, or flagellin prevented the development of mechanical allodynia and spinal microglial activity after MIA injection. Elevated levels of ATP in the cerebrospinal fluid (CSF) and increased expression of the ATP transporter vesicular nucleotide transporter (VNUT) in the ipsilateral spinal dorsal horn were also observed after MIA injections. Selective silencing of primary joint afferents subsequently inhibited ATP release into the CSF. Furthermore, increased spinal microglial reactivity, and alleviation of MIA-induced arthralgia with co-administration of QX-314 with bupivacaine were recapitulated in female rats. Our results demonstrate that early peripheral joint injury activates joint nociceptors, which triggers a central spinal microglial response. Elevation of ATP in the CSF, and spinal expression of VNUT suggest ATP signaling may modulate communication between sensory neurons and spinal microglia at 2 weeks of joint degeneration.